A note on improving the mechanism of pinger attachment for the Danish North Sea gillnet fishery - Larsen, Finn (J. Cetacean Res. Manage., 2023)
This paper describes development of a better mechanism for the attachment of pingers to fishing gear, aimed particularly at the Danish bottom-set gillnet fishery. In a cooperative effort involving gillnet fishermen, the fishermen’s organisations and researchers, modifications to the physical shape of a pinger and its attachment to the gear were developed, taking into consideration the acoustic functioning of the pinger, battery life, robustness to operational rigours, weight, volume, buoyancy, environmental effects, cost and handling. The suggested attachment (THOR-1) has a number of important advantages in this fishery compared to the more common head rope attachment. THOR1 was tested for ease of handling on board a gillnet vessel and found to perform very well, with minimal interference with normal fishing operations. The main disadvantage of THOR-1 is the need for an effective range of around 200m.